2020
DOI: 10.1016/j.soncn.2020.151051
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physical and Mental Health in Patients with Prostate Cancer Undergoing Androgen Deprivation Therapy: Strategies to Promote and Improve Physical Activity Quality and Quantity

Abstract: Objective: Prostate cancer continues to be one of the highest incident cancers among men.Reducing serum testosterone with androgen deprivation therapy (ADT) is a common effective treatment. While well demonstrated for cancer suppression, there are numerous adverse effects caused by ADT that can contribute to short-and long-term prognosis. Increased levels of physical activity (PA) during treatment may reduce these side effects, however uptake of PA is low. The purpose of this review is to identify and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Health Psychology Research other studies notating the benefits that physical activity and avoiding sedentary behavior has on mental health: one study discussed the benefits of physical activity for PCa patients undergoing ADT and another study reported that lower levels of aerobic exercise was associated with reduced physical and mental health for PCa patients with bone metastases. 49,50 In conclusion, for PCa patients, we found a greater number of studies citing associations with mental health effects and incidence for MHI post-interventional treatment such as RP, RT, and ADT given QoL marker changes. However, one study noted on potential greater incidence for anxiety post AS.…”
Section: Mental Health In Urologic Oncologymentioning
confidence: 83%
“…Health Psychology Research other studies notating the benefits that physical activity and avoiding sedentary behavior has on mental health: one study discussed the benefits of physical activity for PCa patients undergoing ADT and another study reported that lower levels of aerobic exercise was associated with reduced physical and mental health for PCa patients with bone metastases. 49,50 In conclusion, for PCa patients, we found a greater number of studies citing associations with mental health effects and incidence for MHI post-interventional treatment such as RP, RT, and ADT given QoL marker changes. However, one study noted on potential greater incidence for anxiety post AS.…”
Section: Mental Health In Urologic Oncologymentioning
confidence: 83%
“…First, the quality of the included literature needs to be analyzed in terms of reliability. All the included studies were RCTs with the highest experimental grade, and all the studies were conducted in strict accordance with the established process for randomized controlled trials ( 45 ), except for four experimental designs with unclear random assignment methods and blinding points ( 11 , 27 , 33 , 37 ). The included studies were reliable, with more than 70% to ensure a low risk of bias.…”
Section: Discussionmentioning
confidence: 99%